An Escherichia coli mutant quinol:fumarate reductase contains an EPR-detectable semiquinone stabilized at the proximal quinone-binding site - Hägerhäll, C; Magnitsky, S; Sled, V D; Schröder, I; Gunsalus, R P; Cecchini, G; Ohnishi, T (The Journal of biological chemistry, 1999)
The EPR and thermodynamic properties of semiquinone (SQ) species stabilized by mammalian succinate:quinone reductase (SQR) in situ in the mitochondrial membrane and in the isolated enzyme have been well documented. The equivalent semiquinones in bacterial membranes have not yet been characterized, either in SQR or quinol:fumarate reductase (QFR) in situ. In this work, we describe an EPR-detectable QFR semiquinone using Escherichia coli mutant QFR (FrdC E29L) and the wild-type enzyme. The SQ exhibits a g = 2.005 signal with a peak-to-peak line width of approximately 1.1 milliteslas at 150 K, has a midpoint potential (E(m(pH 7.2))) of -56.6 mV, and has a stability constant of approximately 1.2 x 10(-2) at pH 7.2. It shows extremely fast spin relaxation behavior with a P(1/2) value of >>500 milliwatts at 150 K, which closely resembles the previously described SQ species (SQ(s)) in mitochondrial SQR. This SQ species seems to be present also in wild-type QFR, but its stability constant is much lower, and its signal intensity is near the EPR detection limit around neutral pH. In contrast to mammalian SQR, the membrane anchor of E. coli QFR lacks heme; thus, this prosthetic group can be excluded as a spin relaxation enhancer. The trinuclear iron-sulfur cluster FR3 in the [3Fe-4S](1+) state is suggested as the dominant spin relaxation enhancer of the SQ(FR) spins in this enzyme. E. coli QFR activity and the fast relaxing SQ species observed in the mutant enzyme are sensitive to the inhibitor 2-n-heptyl-4-hydroxyquinoline N-oxide (HQNO). In wild-type E. coli QFR, HQNO causes EPR spectral line shape perturbations of the iron-sulfur cluster FR3. Similar spectral line shape changes of FR3 are caused by the FrdC E29L mutation, without addition of HQNO. This indicates that the SQ and the inhibitor-binding sites are located in close proximity to the trinuclear iron-sulfur cluster FR3. The data further suggest that this site corresponds to the proximal quinone-binding site in E. coli QFR.